Constitutional limits to European integration in the New Member States after the biggest enlargement - Sarrión, Joaquín (Economics and Business Review, 2014)
We live in the Europe Union (EU) in a context of relations between legal systems of different levels. Therefore the positions of EU New Member States Constitutional or Supreme Courts are analysed in the paper with the use of the multilevel constitutionalism theoretical approach and focus on changes introduced by the Lisbon Treaty, that opened a new constitutional horizon in the EU integration process. The European Court of Justice (ECJ) defined relations between EU law and national law thanks to the primacy principle of EU law. Nevertheless the EU law's formal authority does not depend exclusively on ECJ position. It is conditioned largely by characteristics of each national legal system and national supreme or constitutional court case law. In fact, in most of EU Member States, certain constitutional reserves or constitutional limits to the primacy of EU law in the constitutional and supreme court case law with regard to (constitutional) fundamental rights and principles, can be found. The paper analyses the origin and development of those limits in the case law doctrine of Constitutional Courts in two old and three new EU Member States and concludes with the identification of the consequences and perspectives of EU integration with regard to the coherent protection of fundamental (constitutional) rights and principles across the EU. (original abstract)